FOLK AND TRADITIONAL MUSIC OF THE WESTERN CONTINENTS by Bruno Nettl. Prentice-Hall, History of Music Series, Englewood Cliffs, New Jersey, revised edition 1973 (original edition 1965) - Tracey, Hugh (International Library of African Music, 1973)
pages: 100
Keywords: African Music